2010
DOI: 10.1074/jbc.m110.128298
|View full text |Cite
|
Sign up to set email alerts
|

NMR Solution Structure and Biophysical Characterization of Vibrio harveyi Acyl Carrier Protein A75H

Abstract: Bacterial acyl carrier protein (ACP) is a highly anionic, 9 kDa protein that functions as a cofactor protein in fatty acid biosynthesis. Escherichia coli ACP is folded at neutral pH and in the absence of divalent cations, while Vibrio harveyi ACP, which is very similar at 86% sequence identity, is unfolded under the same conditions. V. harveyi ACP adopts a folded conformation upon the addition of divalent cations such as Ca 2؉ and Mg 2؉ and a mutant, A75H, was previously identified that restores the folded co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 49 publications
5
31
0
1
Order By: Relevance
“…In comparison with the B. subtilis ACP structure, the distinctive 55 , showed uniform R 2 value because proline had a tendency to form a rigid bent structure in the loop in our previous study (59). These results imply that the Ile 57 and Ser 58 loop region might have a conformational exchange to release and accept the acyl chain and generate enough room to accommodate the longer acyl chains.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In comparison with the B. subtilis ACP structure, the distinctive 55 , showed uniform R 2 value because proline had a tendency to form a rigid bent structure in the loop in our previous study (59). These results imply that the Ile 57 and Ser 58 loop region might have a conformational exchange to release and accept the acyl chain and generate enough room to accommodate the longer acyl chains.…”
Section: Discussionmentioning
confidence: 82%
“…However, both results confirmed that the T m of Ec-ACP in the presence of Ca 2ϩ was Ͼ12°C higher than that of Ec-ACP in the absence of metal ions. Also, it has been reported that V. harveyi ACP has an ␣-helical structure with a T m value of 66.4°C in the presence of Ca 2ϩ , whereas this protein is unfolded in the absence of Ca 2ϩ (58). The measurement of melting temperatures implied that Ef-ACP has much higher thermal stability than does other ACPs.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations